Cognitive Improvement Of Students Through Empowerment Of Physical Education Technology Based On Interactive Gysternal Learning Media: Peningkatan Kognitif Mahasiswa melalui Pemberdayaan Teknologi Pendidikan Jasmani Berbasis Media Pembelajaran Interaktif Senam - Jori Lahinda; Pulung Riyanto (Journal of Physical and Outdoor Education, 2022)
This research is a quantitative descriptive study using a variable, namely cognitive ability. The sample used in this study amounted to 63 respondents. The research instrument used in collecting data is a questionnaire or questionnaire. To analyze the collected data, the researcher used ANOVA analysis with SPSS version 25 software. The aim of the study was to find out the cognitive improvement of students through the empowerment of physical education technology based on interactive gymnastics learning media. The results showed that if there was an increase in students' cognitive abilities in empowering physical education technology based on interactive learning media, which was shown from 63 physical education students at Musamus University, 49 students (77.78%) were in the very high category, 6 students (9.53%) were in the high category, 4 students (6.35%) were in the moderate category, 2 students (3.17%) were in the low category and 2 students (3.17%) were in the very low category. So that the average cognitive ability of students through the empowerment of physical education technology based on interactive learning media is in the very high category